Sirtuin 3 is required for the dexmedetomidine‐mediated alleviation of inflammation and oxidative stress in nephritis - Kai Lu; Xinlong Li; Jie Wu (Immunity, Inflammation and Disease)
Abstract Introduction Although sirtuin 3 (SIRT3) is known to be involved in dexmedetomidine (DEX)‐mediated alleviation of renal ischemia and reperfusion injury, the influence of the association between DEX and SIRT3 on nephritis development remains unclear. In this study, the role of SIRT3 in DEX‐mediated amelioration of inflammation and oxidative stress in nephritis as well as the possible underlying mechanism were explored in vivo and in vitro. Methods An animal model of glomerulonephritis was generated by injecting mice with interferon‐alpha (IFNα)‐expressing adenoviruses, and periodic acid–Schiff staining was then used to reveal pathogenicity‐related changes in the renal tissue. Additionally, human embryonic kidney cells (HEK293) and renal mesangial cells (RMCs) were treated with IFNα to establish cell models of inflammation in vitro. Results DEX administration alleviated glomerulonephritis in the animal model and upregulated SIRT3 expression in the renal tissue. SIRT3 knockdown inhibited the renoprotective effects of DEX against nephritis. IFNα induced inflammation, oxidative stress, and apoptosis in the RMCs and HEK293 cells and reduced their growth, as evidenced by the evaluation of cytokine levels (enzyme‐linked immunosorbent assay), reactive oxygen species generation, catalase and superoxide dismutase activities, nuclear factor‐erythroid factor 2‐related factor 2/heme oxygenase‐1 signal transduction, apoptotic cell proportion, and cell viability. In addition to promoting SIRT3 expression, DEX inhibited IFNα‐induced inflammation, oxidative stress, and apoptosis in these cells and promoted their viability. SIRT3 knockdown partially reversed the beneficial effects of DEX on RMCs and HEK293 cells. Conclusions Our results suggest that DEX exhibits renoprotective activity during nephritis progression, protecting renal cells against inflammatory injury by promoting SIRT3 expression.